MANFAAT KPP BAGI PASUTRI KATOLIK YANG MELANGSUNGKAN PERNIKAHAN ADAT KENDAWANGAN SEBELUM MENERIMA SAKRAMEN PERKAWINAN - Ira Mardila; Albert I Ketut Deni Wijaya (Bahasa Indonesia, 2022)
Marriage preparation course program is a preparatory stage for Catholic married couples in preparing themselves for the sacramental marriage. However, the phenomenon that occurred at the St. Lukas Teluk Batu Parish of Kanak-Kanak Yesus Marau nowadays many married couples are married in a traditional way before attending the Marriage Preparation Course and getting married in a sacramental manner. This is the author's concern, which raises several questions, namely what are the views of Catholic couples about the benefits of Marriage preparation course Program. The results of the study show that showed that Marriage preparation course Program give beneficial for their married life. The benefits that respondents often feel are that it helps them communicate in the family, helps in educating their children in a Catholic way, and they know the nature of Catholic marriage. In addition, this husband and wife generally have a traditional marriage before the sacrament marriage. The reason for this is because of traditional traditions and pregnancy out of wedlock. By now, they had all performed a sacramental marriage. This they do with the aim that their marriage is recognized by the Church and the state.